Human milk‐sharing practices and infant‐feeding behaviours: A comparison of donors and recipients. Issue 4 (27th June 2022) - Peregoy, Jennifer A.; Pinheiro, Giovana M.; Geraghty, Sheela R.; Dickin, Katherine L.; Rasmussen, Kathleen M.
Abstract: Human milk sharing (HMS) is growing in popularity as an infant‐feeding strategy in the United States. HMS families are a hidden population because HMS is a nonnormative and stigmatized behaviour. Thus, gaining access to HMS participants is challenging, and research on this topic remains limited. In particular, little is known about the broader infant‐feeding behaviours of HMS parents. This study aimed to describe and compare the infant‐feeding behaviours and HMS practices among a network of HMS donors and recipients. A detailed online survey was distributed to HMS parents in the Washington, DC region. Bivariate analyses were used to summarize the data by donor/recipient status when possible. Group differences were tested using analysis of variance for continuous variables and χ 2 tests for categorical variables. Donors and recipients did not differ in their sociodemographic characteristics. Recipients were significantly more likely than donors to have experienced complications of labour and delivery, traumatic birth, postpartum depression or a negative breastfeeding experience. Donors and recipients did not differ significantly in their duration of lactation or HM‐feeding. Interestingly, 30% of recipients ever produced excess milk and 21% of donors ever had difficulty producing enough milk for their child. Compared with donors, recipients faced numerous maternal health challenges, but were still able to achieve a long duration of HM‐feeding. HMS recipients represent a vulnerable group who may benefit from additional psychosocial and lactation support to improve their health and breastfeeding outcomes. Additional research is needed to investigate the associations between HMS participation, infant‐feeding behaviours and lactation outcomes. Key messages: All human milk sharing (HMS) participants achieved a long duration of HM‐feeding, reflecting a high value placed on HM and a strong commitment to HM‐feeding. Recipients in this sample were largely using HMS as a strategy to supplement the mother's own milk. Approximately one‐third of recipients ever produced more HM than needed and one‐fifth of donors ever had difficulty producing enough milk, suggesting that both donors and recipients experienced breastfeeding challenges. Many HMS recipients encountered compounded maternal medical and mental health challenges and would therefore benefit from additional psychosocial and lactation support to improve their mental health and breastfeeding outcomes.